ADAPTASI ISTILAH EKONOMI DALAM KOSAKATA BAHASA INDONESIA - Musa, Subirman (Jurnal Ilmiah Administrasita, 2014)
This research aimed to know economics terms which used in everyday while in written media, electronic media, and also in verbal interaction. All of terms be seen if Indonesian vocabularies developed. To catch some information about economics terms, the writer chosed library method with observing and noting the all terms of economics through out of medias (written, electronic) and social interaction. What the writer analyzed, the writer caught 203 economics terms which used, but only 77 terms or 34.94 percent usually used in communication everyday. It pointed that economics contributed a lot in Indonesian vocabularies developed.